Podcasts as Multimedia and Transmedia Experiences: A comparative analysis of portuguese and brazilian podcasts - Raposo, Rui (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This article presents the results of a comparative analysis where a sample of 20 portuguese and brazilian podcasts was deconstructed and where it was possible to identify a wide set of variables worked on or omitted in them. The chosen podcasts dominated, at the time, the list of podcasts with the largest audience produced in Portugal and in Brazil. The results enabled the researchers to better understand some of the structuring indicators inherent to podcasts and, at the same time provide some insight as to the leading podcasts in both the portuguese and the brazilian podcast landscape.